Cocoa and Dark Chocolate Polyphenols: From Biology to Clinical Applications - Magrone, Thea; Russo, Matteo Antonio; Jirillo, Emilio (Frontiers in Immunology, 2017)
It is well known that cocoa and dark chocolate possess polyphenols as major constituents whose dietary consumption has been associated to beneficial effects. In fact, cocoa and dark chocolate polyphenols exert anti-oxidant and anti-inflammatory activities switching on some important signaling pathways such as Toll-like receptor 4/Nuclear factor B/Signal transducer and activator of transcription. In particular, cocoa polyphenols induce release of nitric oxide (NO) through activation of endothelial nitric oxide synthase which, in turn, accounts for vasodilation and cardioprotective effects. In the light of the above described properties, a number of clinical trials based on the consumption of cocoa and dark chocolate have been conducted in healthy subjects as well as in different categories of patients, such as those affected by cardiovascular, neurological, intestinal and metabolic pathologies. Even if data are not always concordant, modifications of biomarkers of disease are frequently associated to improvement of clinical manifestations. Quite interestingly, following cocoa and dark chocolate ingestion cocoa polyphenols also modulate intestinal microbiota, thus leading to the growth of bacteria which trigger a tolerogenic anti-inflammatory pathway in the host. Finally, many evidences encourage the consumption of cocoa and dark chocolate by aged people for the recovery of the neurovascular unit.